Evaluación de la calidad sanitaria del agua de las playas turísticas del Caribe Norte Colombiano (2019)
In the present investigation the sanitary quality of 19 beaches of the Colombian North Caribbean was evaluated, for this the presence of the microbiological parameters Fecal Coliforms, Total Coliforms, Enterococcus and Fungi were determined, using the techniques of membrane filtration and pour plate according to the established in the national and international guides and standards. In the same way, the type of contamination was determined through the relation between Escherichia Coli/Enterococcus, identifying that it is through animal and human sources for the wastewater discharges and inadequate disposal of solids wastes. The most affected beaches by the high concentrations of microorganisms were Crespo (greater than 100 UFC/100 mL of Enterococcus), Punta Arena A (greater than 100 UFC/100 mL of Enterococcus) and Riohacha (greater than 250 UFC/100 mL of Fecal Coliforms). Taking into account the georeferencing of the sampled points, it is evident that the quality is good for most of the beaches with the Fecal Coliforms indicator, the sanitary quality is regular on the beaches of the Magdalena department in relation to the Enterococcus indicator and the presence of fungi was mainly identified in the departments of Atlántico and Bolívar. Therefore, it is necessary to implement controls on the possible sources of pollution that influence the reduction of the quality of the clowns of the Colombian North Caribbean and that can cause diseases to tourists.